Non Solo Vincoli in Rete - Gisella Capponi (mediaGEO soc. coop., 2018)
The potential and evolution of a powerful territorial information tool useful for the knowledge, monitoring, conservation and enhancement of the Italian cultural heritage: La Carta del Rischio and the web-portal Vincoli in Rete. Accessibility and interoperability of data become a fundamental element, especially in emergency situations that require rapid access to information, but also during the normal protection of cultural heritage.